THE IMPACT OF AIR, SOIL, AND WATER POLLUTION ON PUBLIC HEALTH IN MODERN CONDITIONS AND WAYS TO ADDRESS THEM - Yuldasheva F. U.; Akthamova S. U.; Bazuova M. A.; Karimov M. A.; Kalkhorazova Kh. A. (The Conference Hub, 2025)
Pollution of atmospheric air, soil, and water resources significantly worsens public health, leading to an increase in respiratory and cardiovascular diseases, as well as higher economic costs for healthcare and ecosystem restoration. In particular, the rising concentration of harmful substances in the air—such as sulfur dioxide, carbon dioxide, and fine particulate matter (PM2.5)—contributes to chronic respiratory diseases, including asthma, bronchitis, and chronic obstructive pulmonary disease (COPD).